Análise dos resíduos gerados por uma instituição de saúde de grande porte do triângulo mineiro - Oliveira, Larissa Teixeira de (2017)
The present work is a study on the Waste Management of the Health and Biosafety Services of a large hospital in the Triângulo Mineiro. One qualitative analysis was carried out, initially, with the purpose of recognizing the nonconformities that exist in relation to the current legislation related to the subject in question. Subsequently, proposals for improvements to the top management of the establishment were presented, which were successful, and approved in the execution. So, educational posters were developed, presented in them the Waste Groups, in order to assist the professionals in the correct segregation; training and recycling in order to reduce the nonconformity indexes, financial expenses with waste, and provide better Biosafety conditions to the establishment, its employees and service providers. Then, a new data collection was performed to evaluate what had improved in the GRSS in the establishment. In the face of all the improvement proposals, considerable results were obtained, such as reduction in Non-Conformity rates for both GRSS in 63,6% and Biosafety in 78,6%; in the amount of waste generated in Groups A and D, the Group A in the first half of 2016 for the first half of 2017 shows a reduction of 11,67% in waste generation and in Group D of approximately 30% , as well as a reduction in the rates of sharps injuries.